Diversidade genética e estruturação populacional do lobo-marinho-de-Galápagos, Arctocephalus galapagoensis - Lopes, Fernando Ricardo Vieira (2015)
The Galapagos fur seal, Arctocephalus galapagoensis, shows one of the most restricted species distribution range under the Otariidae family, with its distribution restricted to northwest of Galapagos Islands. Among the major threats to the conservation of Galapagos fur seals was the exploitation, that almost drove the species to extinction in the early nineteenth century due to the high economic and subsistence value of its skin and blubber. Currently, the species faces frequents events of El Niño that affect the base of the food chain in the equatorial Pacific Ocean, consequently the predatory and top predatory species like the fur seals. Both hunting and El Niño events led the species to Red List of Endangered Species of International Union for Conservation of Nature, indicating a ≥50% of population in the last 30 years. However, until now, there are no studies related to conservation problems and genetic variability and how genetic variability is represented in the space along the distribution range of Galapagos fur seal. To access the information about genetic diversity, population structure and demographic oscillation as well as how genetic variability is represented in the space we used molecular techniques applying two kinds of markers: a mitochondrial marker (control region, maternal inheritance) and nuclear marker (18 microsatellites loci, bi parental inheritance). The fur seals were sampled in the three major Galapagos fur seals colonies: Cape Hammond (Fernandina Island), Banks Bay (Isabela Island) and Cape Marshall (Isabela Islands). Our results showed that there is a strong female natal fidelity with 33.9% of mtDNA occurring among partitioned colonies. In this sense, this natal philopatry, was converted in fine-scale matrilineal population structure. In the other hand, the population structure inferred by nuclear loci was week. This suggests that males are the main responsible by gene flow among sampled localities, even in a highly mobile species like Galapagos fur seal. Here we discuss the importance of natal philopatry and fine-scale matrilineal population structure of Galapagos fur seal species and their implications for management and conservation in the one of the most representative wildlife sanctuaries, the Galapagos archipelago.